Medication Errors in the Operating Room: An Analysis of Contributing Factors and Related Drugs in Case Reports from a Japanese Medication Error Database. Issue 2 (3rd March 2022) - Suzuki, Ryohei; Imai, Tsuneo; Sakai, Takamasa; Tanabe, Kouichi; Ohtsu, Fumiko
Abstract : Objective: The aim of this study was to prevent drug-related medication errors in the operating room by clarifying the association between the medication error category with related drugs and contributing factors. Methods: We used data from the Japan Council for Quality Health Care's open database on the web. We researched the medication error category, related drugs, and contributing factors. We classified each medication error category into case groups and other medication error categories into control groups. We compared the medication error factors of the 2 groups using multivariate logistic regression analysis on the medication error factors. Results: The total number of analyzed cases was 541. Incorrect dose was the most common medication error category in 170 cases, followed by incorrect drug in 152 cases. Medication error factors (odds ratio, 95% confidence interval) that were found to be significantly positively associated with incorrect dose were "pressor drugs" (3.0, 1.4–6.4), "anesthesia-inducing drugs" (6.3, 1.7–23.4), "lack of knowledge" (2.0, 1.3–3.3), and "drug administration" (3.4, 1.6–7.4). The medication error factors that were found to be significantly positively associated with incorrect drug were "preparation" (5.7, 3.1–10.5) and "medication passed or picked up" (102.2, 35.7–292.8). Conclusions: Medication errors are frequently occurring during drug preparation and administration in the operating room. Medical staff should thoroughly learn about operating room–specific drugs and closely monitor every step of the drug preparation and administration process. It is also important to create a workflow and improve the environment so that it reduces the likelihood of medication errors.